In vitro evaluation of dentin tubule occlusion by three bioactive materials: A scanning electron microscopic study - Ghafournia, Maryam (Dent Res J (Isfahan), 2019)
BACKGROUND: Dentin hypersensitivity (DH) is a common problem characterized by a short, sharp pain. Reduction of dentin permeability by occluding dentin tubules is considered as a method for treating DH. Many substances are available to decrease hypersensitivity. The aim of this study is to evaluate the ability of three different remineralizing agents for occluding dentinal tubules in comparison with positive and negative controls. MATERIALS AND METHODS: In this in vitro scanning electron microscopic (SEM) study, 75 extracted premolars were cut into crown and root fragments with a bur and divided into five groups: group 1: Sodium fluoride 5% varnish was applied (positive control), Group 2: No treatment (negative control), Group 3: Treated with Remin Pro (contains hydroxyapatite and fluoride), Group 4: Treated with MI paste (contains casein phosphopeptide-amorphous calcium phosphate [CPP-ACP]) and Group 5: Treated with GC tooth mousse (contains CPP-ACP). SEM images were obtained and mean tubular diameter was measured in each group. One-way ANOVA and Duncan's tests were used for statistical analysis. A significant level of α = 0.05 was set for comparison between the groups. RESULTS: Statistically significant difference was observed between Group 2 (negative control) and other four groups (P < 0.05). There was no significant difference between Groups 1, 3, 4, and 5 (P > 0.05). CONCLUSION: Under the limitations of the present in vitro study, it can be concluded that the application of a CPP-ACP paste as well as a paste which contains fluoride is effective on reduction of dentin permeability.